Pengelolaan Bank Sampah Dalam Upaya Peningkatan Pendapatan Keluarga: Studi Pada Bank Sampah Seroja Asri RW 09 Kelurahan Sukorejo Gunungpati Semarang - Sabtarini Kusumaningsih; Titik Rianawati (Universitas Sains dan Teknologi Komputer, 2023)
The purpose of this research is to find out how the community, especially mothers, manage waste so that it is efficient and can be used as additional family income through a container called “ Bank Sampah”.. The method used in this study is a qualitative descriptive method by utilizing qualitative information or data which is described descriptively with the intention of exploring a phenomenon or social reality. The variables used in this research are management, “Bank Sampah”, increased revenue, family. The result of this research is that by managing waste appropriately, the results can help the community increase family income.